Recent trends in structural design of ultra-light refrigerated semitrailers. (1st January 2001) - Bergamini, G.; Ciavarella†a, M.; Demelio, G.
The need for weight reduction has recently motivated the use of better steels to produce lighter chassis in semitrailers lorries, and the resulting chassis are also inevitably more flexible. On the other hand, body structures are made with improved composite materials, so that the weight reduction often corresponds to an increase in rigidity. The combination of these two changes has made the chassis-body ensemble design more complex than it used to be when chassis were extremely rigid, so that there was no major interaction in their structural behaviour with the bodies, and "beam theory" (or at most "plate theory") was more than sufficient to design safely. Here a structural analysis using the Finite Element Method (FEM) is presented, using examples with different chassis with a particular composite material body. The distribution of loads between body and chassis and the amount of structural coupling have been determined when the stiffness of the chassis is reduced. It is found that safe ultra-light designs can be achieved only with a detailed investigation of the stresses acting on the fasteners in the fifth wheel zone. Within such limits, very high global weight reduction can be achieved, with evident advantages for the payload, and at the same time increased safety margins.